EFFECT OF MATERNAL ANAEMIA ON BIRTH WEIGHT - Ahmad, Muhammad Owais; Kalsoom, Umay; Sughra, Ume; Hadi, Usman; Imran, Muhammad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Anaemia is a common medical problem in pregnancy. The extent up to which, maternal anaemia effects maternal and neonatal health is still uncertain. Maternal anaemia is commonly considered a risk factor for low birth weight (LBW) babies. Some studies have demonstrated a strong association between low haemoglobin before delivery and LBW babies. However, others have not found a significant association. Therefore, there is insufficient information to assess the overall adverse impact of anaemia during pregnancy. The aim of this study was to determine whether maternal anaemia would affect the birth weight of the baby and compare this with that of non-anaemic mothers. It was a cross-sectional comparative study carried out at the maternity ward of Fauji Foundation Hospital, Rawalpindi. Methods: One hundred subjects divided into two groups each containing 50 subjects on the basis of consecutive non probability sampling were included in the study. Group-A included 50 Anaemic pregnant women and Group-B 50 non-anaemic pregnant women. Information was collected by direct interviewing method through a precoded structured questionnaire. The Hb level and birth weights were taken from the labour room record. Results: The mean age of the mothers in anaemic group was found to be older than the non anaemic group, i.e., (29.44 versus 27.98), though the difference was statistically non significant. The number of low birth weight infants (64%) was statistically very highly significantly more (p<0.001) in the anaemic group of mothers than the non anaemic group (10%). Conclusion: The results of this study show an association of maternal anaemia in pregnancy with increased risk of LBW babies. Keywords: Maternal anaemia, Perinatal outcome, Low birth weight.